Direct and indirect electrification of chemical industry using methanol production as a case study - Chen, C; Lu, Y; Banares-Alcantara, R (Elsevier, 2019)
This work aims to explore the electrification of chemical industry taking the production of methanol as a case study. A reference process, with a basis of 400,000 tonne per annum, is first simulated in Aspen Plus to produce methanol via traditional natural gas reforming. As an indirect electrification strategy, a non-conventional carbon dioxide hydrogenation methanol plant is then designed to substitute fossil fuel feedstock. Standalone heat-pumps are implemented as a direct electrification method in both processes at various extents generating different scenarios. It has been found that direct electrification has a small impact on energy consumption in all scenarios. In the reference process, direct electrification can only substitute 7.1 MW of heating, accounting for 7.8% of the total heating. In contrast, the energy structure of the indirectly electrified process is completely changed from the reference process: (1) very high temperature heating is eliminated; (2) electricity consumption is increased from 14.2 to 604.1 MW due to feedstock (hydrogen) synthesis. The renewable energy penetration and electricity price are taken into consideration when financial and environmental assessments are performed. At approximately 88% of renewable penetration, carbon neutrality is achieved in the indirectly electrified process. The net present value of the indirectly electrified process breaks even at an electricity price of 22 €/MWh and exceeds its counterpart reference process at 3–4 €/MWh. This analysis will enable the integration and management of renewable energy for methanol production and will facilitate future studies on the electrification of chemical production.